Agenda Setting within ASEAN: Thickening, Broadening, and Breaking Pressures - Ryan Ashley (JAS (Journal of ASEAN Studies), 2023)
The Association of Southeast Asian Nations (ASEAN) is a clear example of an “organized anarchy” within agenda setting literature; meaning that ASEAN has problematic preferences due to its multiple conflicting goals, relies on unclear methods to accomplish those goals, and experiences fluid participation of its members and leaders. This leaves the organization a case study in the path dependency of norms, as ASEAN typically defaults to its founding principles of non-interference, economic inter-connectivity, and regional “centrality” during crises. The research question was on the examples of variation when ASEAN broadens the scope of its mission. The research aimed to answer by framing ASEAN as a subsystem of Southeast Asian regionalism and conducting a comparative historical analysis of three case study periods: the creation of the ASEAN Regional Forum (ARF), the failure to reach a joint communique in 2012 over tensions in the South China Sea, and the ongoing crisis of human rights and governance in Myanmar. The case studies demonstrate that the most effective broadening forces for ASEAN are exogenous. The conclusion argues that this is a problematic status quo for a regional organization that seeks to promote its centrality to counter interference from outside powers.